Can customer relationship management help maximizing revenue management? internship at ap hotels & resorts - Coelho, Bárbara Miranda (2022)
This internship report follows the curricular internship completed at AP Hotels & Resorts as part of the Master's in Management with specialisation in Tourism, taught at the Faculty of Economics of the University of Algarve. The objective of the curricular internship was to apply, in the professional reality and the work context, the knowledge acquired in the academic component of the Master's and, thus, develop practical skills in Revenue Management (RM). This work aims to present the tasks performed during 1560 hours of internship. The report is divided into six main sections: the introduction to the study; the literature review where the main guiding themes of the internship and the elaboration of this report are presented; the research methodology that guided the student's performance during the internship; the characterisation of the company; the presentation of the tasks developed in the internship context; the presentation and discussion of the results; and, finally, the final remarks. This work addressed a gap identified within the company: the need to maximise revenue through customer relationships, which led to an empirical investigation and analysis of Revenue Management, Customer Relationship Management (CRM), and the integration of these concepts. The results allowed to provide strategies that integrate RM and CRM to overcome the limitations of each hotel unit. The completion of the internship proved to be crucial for the development of skills in the area of RM, as it allowed the practical application of the tools acquired during the theoretical component of this Master's degree